An Assessment of the Refugees’ Access to Labor and Housing Markets and Healthcare Services in Turkey from Syrian Refugees’ Perspective - Kargin, Inci Aksu (Border Crossing, 2018)
In March 2011, Syrians engaged in peaceful protests as a means of demanding socioeconomic reform. However, the regime’s response prompted the start of a civil war, which has caused hundreds of thousands of civilians to lose their lives and millions more to seek asylum in neighboring countries, with Turkey serving as the destination for most of Syria’s refugees. This study assesses the Syrian refugees’ experiences as they attempt to navigate the Turkish labor and housing markets and access healthcare services. By conducting semi-structured interviews with 60 Syrian refugees in Hatay and Gaziantep provinces of Turkey, this study has determined that the Syrian refugees in Turkey have been forced to work for less pay than the country’s citizens and without insurance, expected to pay high rents and deposits for housing, and they have experienced numerous problems in accessing healthcare services in Turkey such as having difficulty in accessing proper translation services.